2011
DOI: 10.1111/j.1530-0277.2011.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Text‐Message‐Based Drinking Assessments and Brief Interventions for Young Adults Discharged from the Emergency Department

Abstract: TM can be used to assess drinking in young adults and can deliver brief interventions to young adults discharged from the ED. TM-based interventions have the potential to reduce heavy drinking among young adults but larger studies are needed to establish efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
185
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(188 citation statements)
references
References 33 publications
1
185
1
1
Order By: Relevance
“…Several recent studies have shown that mobile phone‐delivered interventions have the potential to influence drinking behaviour in emergency department attendees 16, 17, 18, college students 19, 20, young people 21, adults 22 and alcohol‐dependent patients 23. Delivering an alcohol brief intervention by mobile phone would be ideal for targeting disadvantaged groups who may be reluctant to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that mobile phone‐delivered interventions have the potential to influence drinking behaviour in emergency department attendees 16, 17, 18, college students 19, 20, young people 21, adults 22 and alcohol‐dependent patients 23. Delivering an alcohol brief intervention by mobile phone would be ideal for targeting disadvantaged groups who may be reluctant to participate in research.…”
Section: Introductionmentioning
confidence: 99%
“…Personalised interventions, including tailored feedback and prompts, was associated with an increase in willingness to reduce alcohol use (Mason et al, 2014), and a reduction in the number of Heavy Drinking Days (HDD) and Drinks Per Drinking Day (DPDD) (Suffoletto et al, 2012;Suffoletto et al, 2015). However, it was found that self-monitoring alone was not effective at decreasing alcohol consumption (Suffoletto et al, 2015).…”
Section: Text Messagementioning
confidence: 92%
“…The act of responding to a series of text messages resulted in a decrease in the number of Heavy Drinking Days and maximum drinks per drinking days (Suffoletto et al, 2012;Suffoletto et al, 2015), whilst booster texts increased intentions to reduce alcohol use (Mason et al, 2014). Consequently, a more interactive approach may prompt the individual to actively consider their current drinking behaviour, almost acting as a 'teachable moment', whereby behaviour change is triggered by a specific event, experience, or as a consequence of risky behaviour (Boudreaux, Bock & O'Hea, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a feasibility trial, young adults screened for hazardous alcohol consumption in emergency departments were asked to report total and maximum singleoccasion drinking each week on either Saturday or Sunday via SMS, with the intervention group sent immediate SMS feedback and advice [8]. They found that the intervention group consumed fewer drinks per drinking day in the last month at follow-up, compared to controls.…”
Section: Introductionmentioning
confidence: 99%